A feasibility study of incorporating Surface Tension Elements to improve the efficiency of residential clothes dryers - Cochran, Michael Patrick (Kansas State University, 2007)
A Surface Tension Element (STE), device was successfully constructed and tested as the primary moisture removal device in a condensing dryer. The STE was tested via the SAE ARP901 bubble-point test method and resulted in an average micron rating of 46.8 microns. The operation of the STE was compared to that of the typical air-to-air heat exchanger/condenser used in condensing dryers. The total power consumption and IEC efficiency of each case were averaged and compared. The results indicated that the STE used an average of 0.616 kilowatt-hours per kilogram dry laundry while the air-to-air heat exchanger/condenser used an average of 0.643 kWh/kg. This resulted in an improvement of the European efficiency label from class C to Class B. An analytical model was also constructed that well predicted the operation of the STE under steady state conditions.
Keywords: Surface tension elements; Humidity Removal; Drying; Engineering, Mechanical (0548)